Temporal and spatial distribution of larval fish assemblage in different ecological habitat in Johor Strait, Peninsular Malaysia - Ara, Roushon; Arshad, Aziz; Sarker, S. M. Nurul Amin Harmuj Ali; Abd. Ghaffar, Mazlan (Academic Journals, 2013)
Fish larval diversity is very important for management of the fisheries resources. Fish larval density, family richness, Shannon Wiener index and evenness were determined by analyzing samples collected from the seagrass-mangrove ecosystem of Gelang Patah, Johor Strait, Peninsular Malaysia between October 2007 and September 2008. Five stations were selected namely upper estuary (S1), middle estuary (S2), lower estuary (S3), seagrass beds (S4) and outside seagrass beds (S5). In total, 24 fish larval families were identified from the investigated area. Among them, 14 occurred in upper estuary, 17 in middle estuary, 16 in lower estuary, 20 in seagrass beds and 16 in outside seagrass beds. Overall five (Clupeidae, Blenniidae, Terapontidae, Gobiidae and Sillaginidae) were the most dominant in study areas. Shannon-Wiener index varied significantly within monsoon and intermonsoon seasons peaking in the months October-January and May-August. The highest density of larval fishes was recorded at seagrass station (S4) and the spatial variations in larval density were significant (p<0.05) between seagrass and other four sampling sides. None of the diversity indices showed significant among-stations except only family richness was significantly (p<0.05) higher in seagrass beds than upper estuary.